'Making the grade': a grounded theory explaining the student experience of Asian and Middle-Eastern postgraduates in a British university. Issue 1 (2nd January 2018) - McMahon, Patrick
ABSTRACT: The aim of this study was firstly to describe the experiences of international students living and studying in a UK university, to understand and explain their responses to those experiences and to make recommendations to stakeholders in the light of the findings. The research found that international students' two biggest concerns are their English language skills and their detachment from domestic students. International students were surprised at the size of the challenges they faced and worked hard to bridge the gap between their academic and sociocultural skills and those needed in the UK. International students provided emotional, practical and academic support to each other, but the academic support they offered to each other was not always reliable. International students engaged in a process of identity change during which they gained the skills they needed to be academically successful. Recommendations in regard to the academic and pastoral support of international students are made.